Rolling-Circle Transposons Catalyze Genomic Innovation in a Mammalian Lineage - Thomas, Jainy; Phillips, Caleb D.; Baker, Robert J.; Pritham, Ellen J. (Genome biology and evolution, 2014)
Rolling-circle transposons (Helitrons) are a newly discovered group of mobile DNA widespread in plant and invertebrate genomes but limited to the bat family Vespertilionidae among mammals. Little is known about the long-term impact of Helitron activity because the genomes where Helitron activity has been extensively studied are predominated by young families. Here, we report a comprehensive catalog of vetted Helitrons from the 7× Myotis lucifugus genome assembly. To estimate the timing of transposition, we scored presence/absence across related vespertilionid genome sequences with estimated divergence times. This analysis revealed that the Helibat family has been a persistent source of genomic innovation throughout the vespertilionid diversification from approximately 30-36 Ma to as recently as approximately 1.8-6 Ma. This is the first report of persistent Helitron transposition over an extended evolutionary timeframe. These findings illustrate that the pattern of Helitron activity is akin to the vertical persistence of LINE retrotransposons in primates and other mammalian lineages. Like retrotransposition in primates, rolling-circle transposition has generated lineage-specific variation and accounts for approximately 110 Mb, approximately 6% of the genome of M. lucifugus. The Helitrons carry a heterogeneous assortment of host sequence including retroposed messenger RNAs, retrotransposons, DNA transposons, as well as introns, exons and regulatory regions (promoters, 5'-untranslated regions [UTRs], and 3'-UTRs) of which some are evolving in a pattern suggestive of purifying selection. Evidence that Helitrons have contributed putative promoters, exons, splice sites, polyadenylation sites, and microRNA-binding sites to transcripts otherwise conserved across mammals is presented, and the implication of Helitron activity to innovation in these unique mammals is discussed.